2016
DOI: 10.5966/sctm.2015-0358
|View full text |Cite
|
Sign up to set email alerts
|

Personalized Stem Cell Therapy to Correct Corneal Defects Due to a Unique Homozygous-Heterozygous Mosaicism of Ectrodactyly-Ectodermal Dysplasia-Clefting Syndrome

Abstract: Ectrodactyly-ectodermal dysplasia-clefting (EEC) syndrome is a rare autosomal dominant disease caused by mutations in the p63 gene. To date, approximately 40 different p63 mutations have been identified, all heterozygous. No definitive treatments are available to counteract and resolve the progressive corneal degeneration due to a premature aging of limbal epithelial stem cells. Here, we describe a unique case of a young female patient, aged 18 years, with EEC and corneal dysfunction, who was, surprisingly, ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 32 publications
(44 reference statements)
0
7
0
Order By: Relevance
“…Very recently, keratoplasty lenticules, a novel carrier, have been proven to be suitable for transplantation to reconstruct the ocular surface and treat LSCD [ 42 ]. Our research team has succeeded in culturing OMECs on acellular porcine corneal stroma (APCS) [ 24 ], and a clinical trial in our hospital has demonstrated that APCS transplantation is useful for treating fungal keratitis [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Very recently, keratoplasty lenticules, a novel carrier, have been proven to be suitable for transplantation to reconstruct the ocular surface and treat LSCD [ 42 ]. Our research team has succeeded in culturing OMECs on acellular porcine corneal stroma (APCS) [ 24 ], and a clinical trial in our hospital has demonstrated that APCS transplantation is useful for treating fungal keratitis [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…All EEC mutants showed defects in stratification and differentiation and shorter lifespans in vitro. 20,21 Nevertheless, in this study we demonstrate that H-LESCs potency and length of lifespan are at least three times lower than H-SESCs (Figure 2), a likely explanation of the early signs of degeneration seen in the ocular surface of patients with EEC syndrome.…”
Section: Discussionmentioning
confidence: 52%
“…This is likely due to the epithelium of the skin being constantly subjected to stress and continuously renewed. 52 In our previous studies, [19][20][21] we provided evidence that a major factor in the pathophysiology of EEC syndrome is the premature degeneration of the limbal epithelial SCs and the palisade structures.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations